Creation of an electronic learner corpus of French as a foreign language - Tsaknaki, Olympia (Taikomoji kalbotyra, 2023)
According to research findings, learner corpora can have many functions in the field of Applied Linguistics. This was the thinking behind the creation of the KPG Learner Corpus of French1. This interlanguage corpus is comprised of written productions in French obtained from Greek-speaking learners/users of French who participated in the differentiated and graded certification examinations for the National Foreign Language Exam System (Κρατικό Πιστοποιητικό Γλωσσομάθειας, ΚΠΓ) in Greece. It is an ongoing project, which, in its present form, is comprised of 630 written productions of Levels A, B and C (165 000 words) covering a period of two years (2018-2019). As regards its potential applicability and value, useful observations could bring to the fore choices, problems and errors relating to the learners’ interlanguage.